Hubungan antara Hardiness dan Kepuasan Kerja pada Perawat di Rumah Sakit X - Riesa Eka Priasmawati; Iman Sukhirman (Jurnal Ilmiah Psikologi MIND SET, 2009)
The purpose of the research is to recognize a positive relationship between hardiness and work satisfaction. This research used correlation design conducted in a natural setting. The participants were the nurses of the X hospital from three units: Emergency, Outpatients, and Inpatients. The number of the subject is 135 participants. The result shows that a positive correlation between hardiness and work satisfaction exists. The positive correlation proves that the relation between the two variables is proportional, i.e. a higher hardiness score means higher work satisfaction score, and vice versa. Therefore, people with high hardiness are more satisfied with their work. Conversely, persons with low hardiness are less satisfied with their job.